Thermal Stability Study on Titanium Disilicide (TISI2) Thin Films with Titanium Nitride (Tin) Capping Using Atomic Force Microscopy - Venezuela, Jeffrey D.G.; Amorsolo, Jr., Alberto V. (Philippine Engineering Journal, 2011)
Titanium disilicide (TiSi2) has largely been used as gates and interconnects in semiconductor devices due to its low resistivity and good thermal stability. This work aimed to study the thermal stability of titanium disilicide thin film capped with titanium nitride based on measurements using the atomic force microscope (AFM) and four-point probe apparatus. Capped and uncapped silicide thin film samples, produced from the same initial thickness of Ti film (60 nm) on (111)-Si substrate but subjected to different rapid thermal processing schemes to form the silicide, were annealed at 950oC at varying annealing times (10, 20, 30, 40, 50 and 120 minutes). Morphological changes associated with thermal degradation were determined using both the AFM and scanning electron microscope (SEM). The changes in both the film’s surface roughness and sheet resistance were also monitored over these annealing times. Results indicate significantly higher root mean square (RMS) surface roughness and sheet resistance in the uncapped sample after 120 minutes annealing implying better thermal stability in the capped than in the uncapped sample. The efficacy of TiN in increasing the thermal stability of TiSi2 is attributed to originate from a retardation of material diffusion in the silicide layer. Also, atomic force microscopy was successfully applied to understand the thermal stability of the TiN-capped silicide.